Implikasi Pendidikan Holistik dalam Pembelajaran Pendidikan Agama Kristen di SMP Kristen Rehobot Oebelo - Dance Manekat Tefbana; Ezra Tari; Hendrik A.E Lao (Didache: Journal of Christian Education, 2022)
Teachers in learning Christian Religious Education have not implemented holistic education. The implementation of the 2013 curriculum used only focuses on the cognitive aspects. This paper aims to determine the application and impact of holistic education implementation in PAK learning. The method used is a qualitative, phenomenological approach. The CE teacher at the Rehoboth Oebelo Christian Middle School has implemented holistic education. This can be seen from the teacher's efforts to develop students' potential well and appropriately and using strategies/methods appropriately and adequately. So that students can be active in class and use the learning environment based on the subject matter and evaluation results.